KEDUDUKAN PERJANJIAN EKONOMI ANTARA PEMERINTAH DAERAH DENGAN LEMBAGA INTERNASIONAL DITINJAU DARI HUKUM NASIONAL DAN INTERNASIONAL - Ananda Jakaria; Jelly Leviza; Arif Arif (Journal of USU International Law, 2013)
ABSTRAKSI The need for relationships between members of a community with other members of society with the growing technological advances in the field of transport, communication and information. In this regard, the government has enacted the Law number 37 of 1999 on Foreign Relations and the Law Number 24 Year 2000 on the International Covenant which is the result of the ratification of the Vienna Convention of 1969 and 1986. The second law provides a strong legal foundation for the organizers of foreign relations, foreign economic cooperation of local governments.Keywords : International Agreements, Local Governments, International Organizations